1994
DOI: 10.1002/yea.320100903
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a set of yeast genes coding for a novel family of putative ATPases with high similarity to constituents of the 26S protease complex

Abstract: There is accumulating evidence for a large, highly conserved gene family of putative ATPases. We have identified 12 different members of this novel gene family (the YTA family) in yeast and determined the nucleotide sequences of nine of these genes. All of the putative gene products are characterized by the presence of a highly conserved domain of 300 amino acids containing specialized forms of the A and B boxes of ATPases. YTA1, YTA2, YTA3 and YTA5 exhibit significant similarity to proteins involved in human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 42 publications
0
77
0
Order By: Relevance
“…Moreover, oxidized proteins are retained by maternal cells so that daughter cells begin with a lower oxidized protein burden (36). There is considerable evidence that the 20S proteasome is responsible for the preferential degradation of oxidatively modified intracellular proteins in the absence of ATP and ubiquitin (22)(23)(24)(25)(26)(37)(38)(39), whereas the 26S proteasome (with or without ATP͞ubiquitin) has only a minimal ability to selectively degrade oxidatively modified proteins (37). In another report, it was demonstrated that the ATP͞ubiquitin-dependent 26S proteasome is very sensitive to direct oxidative inactivation (39), and the oxidative stress eventually suppresses the ubiquitinylation process (40), whereas the 20S proteasome complex is quite resistant (39).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oxidized proteins are retained by maternal cells so that daughter cells begin with a lower oxidized protein burden (36). There is considerable evidence that the 20S proteasome is responsible for the preferential degradation of oxidatively modified intracellular proteins in the absence of ATP and ubiquitin (22)(23)(24)(25)(26)(37)(38)(39), whereas the 26S proteasome (with or without ATP͞ubiquitin) has only a minimal ability to selectively degrade oxidatively modified proteins (37). In another report, it was demonstrated that the ATP͞ubiquitin-dependent 26S proteasome is very sensitive to direct oxidative inactivation (39), and the oxidative stress eventually suppresses the ubiquitinylation process (40), whereas the 20S proteasome complex is quite resistant (39).…”
Section: Discussionmentioning
confidence: 99%
“…Recently two genes, RCA1 and AFG3, were shown to control the assembly of more than one respiratory complex [21]. These genes belong to the AAA protein family and would code for ATP-dependent metallo-proteases required for the degradation of incompletely synthesized or misfolded polypeptides of the mitochondrial inner membrane [22][23][24][25][26][27][28]. The inactivation of RCAI or AFG3 was shown to diminish the NADH cytochrome c oxido-reductase, the cytochrome c oxidase and the ATPase activities, as well as to cause an arrest in assembly of the complexes IlI and IV and to delay the assembly of the F1-ATPase complex components [21,29].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, many subunits of these complexes are quickly degraded in mutants that fail to associate them with their partner subunits. Mitochondrial ATPdependent proteases involved in such degradative processes include Pim1p (33,34) in the matrix and two membraneembedded proteases, Yme1p and Afg3p/Rca1p, of the AAA family of ATPases (35)(36)(37)(38)(39). Pim1p has been implicated in the degradation of imported proteins that fail to fold into a native structure.…”
Section: Ultrastructural and Immunocytochemical Analyses Of The ⌬Fmc1mentioning
confidence: 99%